2005
DOI: 10.2320/matertrans.46.1481
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Properties of (Ti,Zr,Hf)CoSb Type Half-Heusler Compounds

Abstract: Half-Heusler compounds have a possibility as a new thermoelectric material due to the large thermoelectric power and low thermal conductivity derived from the band structure and voids in the crystal, respectively. Among these materials, we have paid attention to (Ti,Zr,Hf)CoSb system, and have investigated the improvement of the thermoelectric figure of merit from the measurements of the electrical resistivity, thermoelectric power, and thermal conductivity. We obtained the largest ZT ¼ 0:027 on TiCoSb at 921 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
25
2
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 34 publications
12
25
2
1
Order By: Relevance
“…It is considered that these Hf-rich impurity phases may induce the reduction of . On the other hand, we have confirmed that the as-cast HfCoSb sample 11) contains the Hf-rich impurity phases in the XRD pattern. It is not always true that just only a segregation of Hf-rich impurity phases is responsible for small .…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations
“…It is considered that these Hf-rich impurity phases may induce the reduction of . On the other hand, we have confirmed that the as-cast HfCoSb sample 11) contains the Hf-rich impurity phases in the XRD pattern. It is not always true that just only a segregation of Hf-rich impurity phases is responsible for small .…”
Section: Resultssupporting
confidence: 63%
“…6) It is considered that the differences of the between the present and previous studies 11) are mainly due to the deviation from the stoichiometric composition as well as the relaxation of the structural disorder effect by annealing.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The relaxed lattice constants of undoped and doped TiCoSb are summarized in Table 1. For Ti/Zr/HfCoSb, the optimized lattice constants are in good agreement with the experimental [25] and other theoretical results [24] [26], with slight overestimates typical of the GGA [27]. The above results indicate that the crystal model was rational and could be used for computational prediction.…”
Section: Crystal Structuressupporting
confidence: 75%